Analisis Perbandingan Kinerja Keuangan Bank Swasta Nasional Dan Bank Pemerintah Yang Terdaftar Di Bursa Efek Indonesia (Bei) - Hastuti, Sri; Ratnawati H, Dyah (AKRUAL: JURNAL AKUNTANSI, 2011)
AbstractPerformance or performance of bank is the image of reached achievement in banking operational in all aspect, covering monetary management of bank and ability of bankâs assets had to yield profit efficiently, so bank can stay and compete in the middle of inflation distortion and policy of Bank Indonesia, hence the bank had to have up to standard performance or performance - condition health of bank determined by Bank Indonesia. This research aim to analyse and prove the difference flattens which isnt it in monetary performance Private National Bank and State Bank pursuant to ratioes of CAMEL. Sampel the used to amount to 12 banks, consist of 9 Private National Bank and 3 taken State Bank pursuant to Purposive Sampling with criterion enlist in Indonesia Stock Exchange (BEI), routine deliver financial statement, period of year 2005-2007.